A new occupational health agenda for a new work environment - Benach, Joan; Muntaner, Carles; Benavides, Fernando G; Amable, Marcelo; Jodar, Pere (Scandinavian journal of work, environment & health, 2002)
At the beginning of the 21st century, the emergence of new forms of work organization are transforming what had become standard types of work arrangements in industrialized countries. In this new labor market environment, new firms, types of workers, and risk factors are powerfully emerging. Contrary to common belief, emergent occupational health hazards should not be approached only as "technical" or "economic" value-free problems. Instead, many of the challenges faced by occupational health policy makers are predominantly related to professional values and to the political ideologies and economic interests of key stakeholders in the decision-making process. In this paper some of the key principles leading to efficient and equitable occupational health policies in the new work environment are discussed. An alternative is also proposed for dealing with the conditions and settings needed to meet the new challenges related to establishing an effective occupational health policy.